Perlindungan Konsumen atas Penggantian Produk tanpa Kesepakatan di Marketplace Shopee Perspektif Fatwa DSN-MUI No. 144/DSN-MUI/XII/2021 - Safitri, Maysarah; Suparmin, Sudirman (AL-SULTHANIYAH, 2025)
One form of consumer loss in the marketplace is caused by the irresponsible actions of business actors regarding the products they sell, specifically the replacement of products without prior agreement. This study aims to analyze consumer protection regarding product replacements without prior agreement on the Shopee marketplace from the perspective of Fatwa DSN-MUI No. 144/DSN-MUI/XII/2021. The research employs a normative legal research method using a statutory approach and a conceptual approach. Data was obtained through a literature review of Fatwa DSN-MUI No. 144/DSN-MUI/XII/2021 on marketplaces based on Sharia principles and other legal sources such as laws, books, journals, and previous studies related to this research. The results of the study indicate that product replacement without agreement can be considered a breach of contract because the business operator has failed to fulfill their responsibilities in accordance with the agreement. Article 7 letter c of the Consumer Protection Law stipulates that business actors have an obligation to treat or serve consumers fairly and honestly, without discrimination. Based on Fatwa DSN-MUI No. 144/DSN-MUI/XII/2021, when selling goods to consumers, business operators are not permitted to engage in actions that contradict Islamic law, namely tadlis (fraud), tanajusy (excessively high prices), and ghisysy (concealing defects in products).